2009
DOI: 10.1007/s00204-009-0485-0
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effects of the antileishmanial drug glucantime®

Abstract: Leishmaniasis is caused by species of the protozoan parasite Leishmania. It is the third most important vector-borne disease and is widely distributed throughout the world. The World Health Organization recommends pentavalent antimonials as drugs of first choice in its treatment. Although Glucantime has traditionally been used to treat leishmaniasis, there are still many questions about its structure, mechanisms of action and ability to induce damage in DNA. In this study, the genotoxic activity of this drug w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 19 publications
4
34
0
3
Order By: Relevance
“…Due to side effects such as high cardiotoxicity, pancreatitis, and nephrotoxicity, patients should be hospitalized and monitored, as treatment may need to be suspended [5,6]. Antimonials seem to have a broad mechanism of action [7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to side effects such as high cardiotoxicity, pancreatitis, and nephrotoxicity, patients should be hospitalized and monitored, as treatment may need to be suspended [5,6]. Antimonials seem to have a broad mechanism of action [7].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the drug of choice that is recommended by the World Health Organization and the Brazilian Ministry of Health, Glucantime ® , an antimonite of N-methylglucamine, has genotoxic and mutagenic activities in vivo (Lima et al, 2010). We showed that the antileishmanial hydroalcoholic extract of T. cinerea (L.) Pers.…”
Section: Discussionmentioning
confidence: 92%
“…Leishmaniasis is an endemic disease in Brazil that is generally treated with Glucantime ® despite its known genotoxic and mutagenic activities in vivo (Lima et al, 2010). To aid the search for new leishmaniasis treatments, we extended a previous study showing that hydroalcoholic extracts of T. cinerea leaves exert a potent antileishmanial activity (Bezerra et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that an agent's capacity to induce genetic damage can be directly related to its metabolism, so the genotoxic effects in vitro may be different than those seen in in vivo assays (Lima et al, 2010). To test whether components in the extract would have a different effect on DNA after metabolism, the genotoxic potential of the extract was tested in Swiss mice.…”
Section: Discussionmentioning
confidence: 99%
“…var. triqueter is a promising phytotherapeutic product for treating leishmaniasis, as it does not show genotoxic effects in vitro or in vivo, contrary to Glucantime ® , the drug currently used to treat this disease, which has a proven mutagenic effect (Lima et al, 2010). In addition, this hydroalcoholic extract is capable of reducing apoptotic cell death and inducing necrotic cell death at anti-leishmanial concentrations.…”
Section: Discussionmentioning
confidence: 99%